A survey on intentional root canal treatment for crown and bridge among dental practitioners - Palaniappan Jaganbabu; Chandrasekaran Ponranjini Vedeswari; Gnanamoorthy Pamalai (Stomatološki glasnik Srbije, 2025)
Introduction/Objective Crown and bridge restorations are commonly used by general dental practitioners to replace partially edentulous areas following operative or endodontic procedures. The main goal was to explore the use of intentional root canal treatment (RCT) for crown and bridge procedures among dental practitioners in Tamil Nadu, India. Methods A total of 124 dental practitioner participated in this questionnaire-based survey. Results The mean duration of practice was 11.66 years; 68.5% responded that they perform intentional RCT in daily practice; 68.3% stated that they undertake RCT only in attrited or mutilated teeth; 62% reported selecting the option "to avoid postoperative sensitivity or pain and to achieve adequate tooth preparation and clearance"; 54% indicated that this preference is based on previous experience. Conclusion Based on this survey, many practitioners prefer intentional RCT before crown and bridge procedures.